Conscientious Autonomy: Displacing Decisions in Health Care - Kukla, Rebecca (The Hastings Center report, 2005)
The standard bioethics account is that respecting patient autonomy means ensuring that patients make their own decisions, and that requires that they give informed consent. In fact, respecting autonomy often has more to do with the overall shape and meaning of their health care regimes. Ideally, patients will sometimes take control of their health care but sometimes defer to medical authority. The physician's task is, in part, to inculcate patients into the appropriate good health care regimes.